2022
DOI: 10.1097/mlr.0000000000001726
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers of Veterans Experience Clinically Significant Levels of Distress Prepandemic and During Pandemic

Abstract: Background: Of the 26.4 million family caregivers in the United States, nearly 40% report high levels of emotional strain and subjective burden. However, for the 5 million caregivers of Veterans, little is known about the experiences of caregivers of Veterans during the coronavirus disease 2019 (COVID-19) pandemic. Objective: The aim was to examine pandemic-related changes of caregiver well-being outcomes. Research Design, Subjects, and Measures: Using a pre/post design and longitudinal data of individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Additionally, some caregivers who felt more hopeful during the pandemic had higher wellbeing (Onwumere et al, 2021). Many of these early studies are limited to comparing caregivers to noncaregivers or using cross-sectional quantitative data during the pandemic only, and were prone to recall bias with methods that relied on caregivers self-reporting perceived changes in wellbeing several months into the COVID-19 pandemic compared to the months before the pandemic (Miller et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some caregivers who felt more hopeful during the pandemic had higher wellbeing (Onwumere et al, 2021). Many of these early studies are limited to comparing caregivers to noncaregivers or using cross-sectional quantitative data during the pandemic only, and were prone to recall bias with methods that relied on caregivers self-reporting perceived changes in wellbeing several months into the COVID-19 pandemic compared to the months before the pandemic (Miller et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…All of these services remained operational during the COVID-19 pandemic with pivots to virtual or phone-based delivery of supports and services. One study of family caregivers of veterans using a pre/post design and longitudinal data showed improved caregiver loneliness and wellbeing compared to before the COVID-19 pandemic; however, while improved, those domains were high before the pandemic and remained so during the pandemic (Miller et al, 2022). While these caregivers continued to experience negative pandemic-related wellbeing effects (Miller et al, 2022), it could be possible that the wellbeing improvements observed were due to VA caregiver services remaining active during the pandemic.…”
Section: Introductionmentioning
confidence: 99%